ALIRAN TERTUTUP MASSA DAN POTENSI MANDIRI ENERGI PADA PRODUKSI CPO - Tajuddin Bantacut dan Hermaslin Pasaribu (Department of Agroindustrial Technology, Bogor Agricultural University, 2015)
Palm oil mill consumes considerable amounts of energy from fossil fuel. The declining of this energy supply in the future becomes a production constraint of palm oil mill. The purposes of this study were to calculate the rational energy needs of CPO production and to assess the energy content of by-products. Mass balance model was developed to illustrate the process flow and to determine the possibility of by-products utilization to meet the energy needs of the mill. The results of the model calculations based on the mill’s rational performance showed that the palm oil mill with a capacity of 60 tons fresh fruit bunches/hour produces crude palm oil at 26.80% yield. This production also generated biomass by-products of empty bunches, fiber, shells, and liquid waste as much as 14,265; 4,613; 1,959 and 21,057 kg/hour respectively. These by-products contained potential energy as much as 271,988,317 kJ/hour. This energy met the need of 1,020 kWh electrical energy and 30 tons of steam with an excess of electricity energy of 1,022 kWh. The electricity surplus might be sold to public network or directly distributed to community around the mill. Biomass electricity generation replaced the coal used and potentially cut the green house gas emission. It was concluded that palm oil mill can be a surplus energy production system. Therefore, it is recommended that palm oil mills should be regulated and restricted in using fossil energy and electricity from public network.Keywords: closed production process, energy self-sufficient, mass balance model, oil palm biomass, palm oil mill